The Gaussian integral states that ∫ − ∞ + ∞ e − x 2 d x = π .
Hence or otherwise, evaluate the integral
∫ − ∞ + ∞ e − x 2 + 2 x + 2 0 1 6 d x
If the above integral can be expressed in the form a e b π , where a , b are positive integers, find a + b .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Similar answer with @Vignesh S 's:
I = ∫ − ∞ + ∞ e − x 2 + 2 x + 2 0 1 6 d x = ∫ − ∞ + ∞ e − ( x 2 − 2 x + 1 ) + 2 0 1 7 d x = e 2 0 1 7 ∫ − ∞ + ∞ e − ( x − 1 ) 2 d x = e 2 0 1 7 ∫ − ∞ + ∞ e − u 2 d u = e 2 0 1 7 π Let u = x − 1 ⟹ d u = d x
⟹ a + b = 1 + 2 0 1 7 = 2 0 1 8
Problem Loading...
Note Loading...
Set Loading...
Write − x 2 + 2 x + 2 0 1 6 as − ( x − 1 ) 2 + 2 0 1 7 and substitute x − 1 = t , the limits of the integral will not be affected. Therefore take e 2 0 1 7 outside, since its a constant , then the integral is nothing but the Gaussian integral